A new species of Polypedates Tschudi (Amphibia, Anura, Rhacophoridae) from Sri Lanka - Wickramasinghe, L. J. Mendis; Munindradasa, D. A. I.; Fernando, Prithiviraj (Zootaxa, 2012)
A new species of frog tentatively assigned to the genus Polypedates is described from the Gilimale forest reserve of theSabaragamuwa province of Sri Lanka. This tree frog is characterized by unique osteological characteristics in the skullwhich distinguish it from all other congeners, such as the presence of a series of maxillary teeth progressively changingorientation from horizontal to vertical from posterior end to anterior; a laterally-curved spine in the quadratojugal bone;and bony co-ossification on the skull resulting in four dorsal spines which are externally seen as protrusions in the parietalarea. Bioacoustic observations of Polypedates ranwellai sp. nov. revealed three distinct call types. High rates of deforestation and anthropogenic activities at the type locality threaten the survival of the species.